From the GATT to the WTO. Does the rule of law matter? Legal order in the consensus based multilateral trading system / Noel Chow Zher Ming - Noel Chow, Zher Ming (2013)
The establishment of the WTO as a permanent institution to oversee the administration of the multilateral trade agreement and the continuing cooperation of its Members in maintaining legal order have prompted diplomats to laud this as an achievement - that the Rule or Law has overcome force or power in presiding over the conditions or international trade. This dissertation begins by tracing the origins of the Rule of Law in search of a meaning in its historical and contemporary context to establish the parameters of the conception of the Rule of Law as a set of doctrinal standards established by previous literature, and then analyses how legal culture, econornic history, socio-political developments and general attitudes or diplomats influenced the contemporary multilateral trade agreements. Subsequently. this dissertation examines the structure of the multilateral trade agreements and case law emanating under its dispute settlement procedures for evidence of implementation and interpretation of the Rule of Law. Then this dissertation will identify unique and perplexing features of GATT/WTO jurisprudence and compare them against the doctrinal Standards which have become infused within the concept or the Rule or Law. Based on these findings, this dissertation concludes with substantial qualifications, that the doctrine or the Rule of Law matters in the administration of the multilateral trade agreements.